Remote Working During COVID-19: BOONS or BANES For Instructors Working in Higher Education Institutions in Pakistan : Analyzing Impact of COVID-19 - Tabassum , Farhana; Baqa, Muhammad Shaghil; Akram, Nazia; Nawaz, Rabia; Bashir, Fareeha; Alam, Mahwish; Sarwar, Zartasha; Jamil, Anam (Pakistan BioMedical Journal, 2022)
Around the world, the Covid-19 pandemic has emerged as the most serious threat to human health, economy, and well-being, affecting substantially every country. The current outbreak has presented society with unexpected obstacles and has jeopardized mankind and global resilience. The present study intends to determine the influence of Covid-19 on 250 educators teaching at various public and private higher educational institutions in Pakistan. An online cross-sectional survey was conducted using a link to a Google questionnaire form. The survey consisted of 20 questions covering demographic information, physical activity, remote working challenges, time spent on social media, and issues with online education. The data were collected using the snowball sampling method, and it was analyzed using SPSS 2021. The findings revealed the detrimental effects of COVID-19 lockdowns, such as excessive use of social media, a sedentary lifestyle, insufficient online classes training,excessive workload, rigorous timetable, the constant worry of shrinking, and wage cutbacks are all factors to consider. To continue the smooth teaching and learning process, the study recommends that educators, government, and policymakersreshape the present policies directly associated with the national teachers' personal, social, economic, physical, and mental well-being.